Effects of parental profession on students' academic performance in financial accounting in Federal Government Colleges, North-West Zone, Nigeria / Dr. Abdulrazak Mohammed and Haruna Hassan - Mohammed, Dr. Abdulrazak; Hassan, Haruna (Universiti Teknologi MARA, Cawangan Melaka, 2022)
This study was conducted to investigate the effects of the parental profession on students‟ academic performance in Financial Accounting in Federal Government Colleges in the North-West zone, Nigeria. The study was necessitated by the continuous decline in students‟ performance in Financial Accounting in Federal Government Colleges in North West zone, Nigeria. The study has one null hypothesis. Five hundred and twenty-nine students from the six Federal Government Colleges in the North-West zone, Nigeria, were used for the study. Regression analysis was used to test hypothesis one at 0.05 level of significance. The entire five null hypotheses were retained. The study revealed among others that: Based on the findings, the study concluded that parental profession has no effect on students‟ academic performance; which means that a child could excel in life irrespective of the type of profession his or her parents are engaged in so long as they can set achievable goal in life. In other words, children could set achievable goals in life. In view of this, the study, therefore, recommends that society should not rank people based on their profession no matter the type of profession they engaged in.